Speech Prosody 2018 2018
DOI: 10.21437/speechprosody.2018-117
|View full text |Cite
|
Sign up to set email alerts
|

Mapping areal variation and majority language influence in North Sámi using hierarchical prosodic analysis

Abstract: We present results of a statistical hierarchical analysis of areal variation in prosody of spoken North Sámi languages. The hierarchical analysis method compares unigram models using cross-entropy measure. The models depict distributions of ∆features of f0 and energy signals decomposed using Continuous Wavelet Transform. These signals are obtained from speech recordings of five areal North Sámi varieties recorded in sites in northern Finland and Norway. We evaluate three potential sources of areal variation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…More recently, a deep network speech synthesis approach—very similar to the present work—was used to find mutual relationships between tonal varieties of Swedish and evaluate the dialectal differences in terms of geographical distribution ( Suni et al, 2019 ). Several studies concentrating on North Sámi, cited above ( Hiovain et al, 2018 ; Jokinen et al, 2016 ; Kakouros et al, 2020 ) are also examples of this approach.…”
Section: Prosodic Typologymentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a deep network speech synthesis approach—very similar to the present work—was used to find mutual relationships between tonal varieties of Swedish and evaluate the dialectal differences in terms of geographical distribution ( Suni et al, 2019 ). Several studies concentrating on North Sámi, cited above ( Hiovain et al, 2018 ; Jokinen et al, 2016 ; Kakouros et al, 2020 ) are also examples of this approach.…”
Section: Prosodic Typologymentioning
confidence: 99%
“… Kakouros et al (2020) investigated the influence of purely prosodic features: energy; fundamental frequency (F0); spectral tilt; duration; and their combinations. In Hiovain et al (2018) , a technique using wavelet decomposition of signals carrying purely prosodic information (F0 contour and energy envelope) showed a greater similarity of varieties spoken in the same country compared to the varieties exposed to the influence of another majority language.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works on North Sámi language varieties, differences between the five dialects have been identified using ivectors [17] and evidence of their typological differences have been observed [18]. In the present study we investigate the potential prosodic differences among the five regional varieties of North Sámi and explore whether the geographical dispersion of North Sámi also underpins disparities in the production of North Sámi that are reflected in the acoustic prosodic characteristics of North Sámi speakers.…”
Section: The North Sámi Language and Dialectsmentioning
confidence: 87%
“…While the methodologies of these papers vary, all of them have used data-driven approaches. Focusing on the spoken varieties of North Sámi, in [21] and [22] it was found that based on prosodic features (f0 and energy envelope) alone, utterances from five areal varieties were clustered following the majority language influence (Norwegian and Finnish) instead of the traditional dialectal groups. When looking at the intonational characteristics of the spoken areal varieties of North Sámi from the two countries, similarities with the respective majority languages were detected from the North Sámi intonational contours extracted from the speech materials.…”
Section: Related Workmentioning
confidence: 99%